Performance Evaluation of the Hedge Funds Established in Turkey - Direkci, Yusuf Emre; Eksi, Ibrahim Halil (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2019)
The aim of this study is to evaluate the performance of the hedge funds in Turkey. Hedge funds, which are quite new to Turkish financial markets, are examined and the performance of the funds that have been founded in Turkey starting from 2008 are analyzed. Analyzed hedge funds, which are in total of 22 funds, are the ones that we have the data for a period of 36 months (2014-2017). The mean returns of the funds and the risks they take are calculated with the use of Istanbul Stock Exchange (BIST100) as a market indicator. Moreover, Data Envelopment Analysis (DEA) has been applied in order to measure the performance of the funds. According to the results, 91% of the funds have been found to have positive monthly geometric return on average. When it comes to the results of DEA, which has been done with 2 different models called BCC and CCR models, the first model has found 55% of the funds efficient whereas the latter has found 41% of them efficient.
Keywords: hedge funds; istanbul stock exchange; geometric mean; data envelopment analysis; efficiency